Exploring Logistics Process Improvement Possibility with SCOR Digital Standard and Lean Waste Analysis - Adhie Prayogo; Curie Habiba; Ulkhaq, M. Mujiya; Dina Tauhida; Sitompul, Fachri Rizky (Journal of Advances in Information and Industrial Technology, 2025)
Inbound logistics, including receiving goods, quality and physical checking, item inquiry, and stock-level checking are essential aspects within supply chain management in which the unresponsive operation may lead to inefficiency. This study aims to observed the ongoing operations in a mid-sized paper manufacturer using a combination of Business Process Modelling to map the current flow process, Lean Waste Analysis to identify possible wastes, and SCOR Digital Standard to offer improvement opportunities. The results show that waiting, motion, overprocessing, and inventory wastes are identified across the three logistics main processes. Additional waste, human skill, is observed in the stock-level checking procedure. Subsequently, SCOR DS recommends the firm to escalate the human skills of lean manufacturing, bar code handling & RFID, ERP system, automation tool, time management, and collaboration, to support the performance improvement. Finally, the study proposed metrics within four dimensions to validate the solution impact on the performance, including the responsiveness, reliability, asset management, and people.